(3YbO GdJQNjU GdJLGQj (B:s "(3OQGSI ebGQfI(B" /s - (3eGgQ, hdjO Ydjs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3jJMOK GdcJGH Yf YbO GdJQNjU GdJLGQj MjK Cf GdJcfhdhLjG gj GdJWHjb GdYedj dKeQGJ GdYde hGcJTGa GdYdeGA hGHJcGQ CaVd GdSHd dGSJYeGdgG hGdGSJaGOI efgG hbO MQUJ GdcKjQ ef GdOhd Cf Jbff GdLhGfH GdbGfhfjI dYedjI fbd GdJcfhdhLjG aj JTQjYGJ MGceI JhaQ MeGjI dCWQGagG hJecfge ef JMbjb GdCgOGa GdJj jUHhf EdjgG ef LQGA gPG Gdfbd hYdi VhA Pdc JfGhd gPG GdcJGH ehVhYGJ GdJcjja GdbGfhfj dfbd GdJcfhdhLjG hYbO GdJQGNjU GdeUGOQ hGdCTcGd GdbGfhfjI ddJcfhdhLjG GdeQNU HgG GdJRGeGJ GdJcfhdhLjG dCWQGa YbO GdJQNjU hGdBKGA hGdLRGAGJ aj YbO GdJQNjU(B.s
(3GdeMJhjGJ (B: (3ebOeI(B-(3GdHGH GdChd (B: (3GdJcjja GdbGfhfj dfbd GdJcfhdhLjG hYbO GdJQGNjU, GdaUd GdChd (B: (3Gdeaghe GdbGfhfj dfbd GdJcfhdhLjG hGdNOeGJ GdafjI GdeYGhfI(B-(3GdaUd GdKGfj (B: (3GdeUGOQ hGdCTcGd GdbGfhfjI ddJcfhdhLjG GdeQNU HgG(B-(3GdHGH GdKGfj (B: (3GdJRGeGJ GdJcfhdhLjG dCWQGa YbO GdJQNjU, GdaUd GdChd (B: (3GdJRGeGJ GdCWQGa GdeHGTQI(B-(3GdaUd GdKGfj (B: (3GdJRGeGJ GdCWQGa GdZjQ eHGTQI(B-(3GdHGH GdKGdK (B: (3GdBKGQ hGdLRGAGJ aj YbO GdJQNjU (B... (3hehVYGJ CNQi(B. s
(3HHdjhLQGajI (B: (3UaMI (B319-338.s
Keywords: (3GdbGfhf GdJLGQjs -- (3eUQs; (3GdYbhO GdJLGQjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3fbd GdJcfhdhLjGs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3HQGAGJ GdGNJQGYs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdedcjI GdUfGYjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdJQGNjU GdJLGQjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3YbO GdJQNjU s; (3fbd GdJcfhdhLjGs; (3YbhO GdJTjjO hGdHfGAs